Octopamine Underlies the Counter-Regulatory Response to a Glucose Deficit in Honeybees (Apis mellifera) - Buckemüller, Christina; Siehler, Oliver; Göbel, Josefine; Zeumer, Richard; Ölschläger, Anja; Eisenhardt, Dorothea (Frontiers in Systems Neuroscience, 2017)
An animal’s internal state is a critical parameter required for adaptation to a given environment. An important aspect of an animal’s internal state is the energy state that is adjusted to the needs of an animal by energy homeostasis. Glucose is one essential source of energy, especially for the brain. A shortage of glucose therefore triggers a complex response to restore the animal’s glucose supply. This counter-regulatory response to a glucose deficit includes metabolic responses like the mobilization of glucose from internal glucose stores and behavioral responses like increased foraging and a rapid intake of food. In mammals, the catecholamines adrenalin and noradrenalin take part in mediating these counter-regulatory responses to a glucose deficit. One candidate molecule that might play a role in these processes in insects is octopamine (OA). It is an invertebrate biogenic amine and has been suggested to derive from an ancestral pathway shared with adrenalin and noradrenalin. Thus, it could be hypothesized that OA plays a role in the insect’s counter-regulatory response to a glucose deficit. Here we tested this hypothesis in the honeybee (Apis mellifera), an insect that, as an adult, mainly feeds on carbohydrates and uses these as its main source of energy. We investigated alterations of the hemolymph glucose concentration, survival, and feeding behavior after starvation and examined the impact of OA on these processes in pharmacological experiments. We demonstrate an involvement of OA in these three processes in honeybees and conclude there is an involvement of OA in regulating a bee’s metabolic, physiological, and behavioral response following a phase of prolonged glucose deficit. Thus, OA in honeybees acts similarly to adrenalin and noradrenalin in mammals in regulating an animal’s counter-regulatory response.